Surgical training and post-surgery evaluation using rapid prototyped biomodels - Queijo, Luis (2011)
The biomedical use of rapid prototyping technologies (RP) had great developments in the last years, especially as supportive tools for tissue growth, direct or supportive technology for implant fabrication or as tool for personalized biomodels production applied to studies, this research will focus on this last type of usage in continuation of previous work developed with RP as an aid of surgery procedures. Biomodels can play an important role as a complementary diagnostic method to medical staff (Queijo et al., 2010). The usage of RP technologies for biomodels production, in Lytic Spondylolisthesis surgical training and as a tool for post-surgery evaluation, is presented in this paper.